Follicle-stimulating hormone receptor gene exploration as possible markers for prolific trait of local goat in Indonesia - E. T. Setiatin; D. A. Lestari; D. W. Harjanti; A. Setiaji; E. Kurnianto (Diponegoro University, 2023)
The objective of this study was to discover and identify the effect of SNP of follicle-stimulating hormone receptor (FSHR) gen on prolific traits in Kejobong (KJ) and Etawah grade (EG) doe. A total of 15 blood samples were taken from 11 KJ and 4 EG with various parity and type of birth. The FSHR gene was amplified from the DNA template by Polymerase Chain Reaction (PCR); the PCR products were then sequenced to determine Single Nucleotide Polymorphisms (SNP). Results showed that 3 SNPs were identified, and those SNPs altered amino acid sequence formed 6 haplotypes and divided the doe based on the type of birth. In conclusion, SNPs identified in this study are associated with a prolific trait that can be used as a genetic marker and haplotype 3, 4, and 5 showed the highest prolific on KJ and EG doe.